La ricerca del falso: Le Prefazioni di Henry James - Rubeo, Ugo (Status Quaestionis, 2016)
Reversing the title of Agostino Lombardo’s well-known text La ricerca del vero, and in light of the scholar’s life-long interest in American literature in general and in Henry James’s work in particular, this essay investigates the meaning of “fiction” as “fabrication” and “false” in James’s Prefaces. Translating and studying the Prefaces, Lombardo was able to appreciate James’s desire to reach the peak of art, finding in the American author’s effort a similarity to his own work as a critic. In fact, James’s reflection on art – which pervades both his essays and his fictional texts and which forms the focus of Lombardo’s critical approach – discloses the importance of the artist himself, who, while narrating a story, reflects on the complexity of the craft of writing. Thus, the Prefaces reveal the artist’s “fraud” and stand as an effective tool through which he attempts to search for the “false” in order to attain to truth.